Pressure vessel design by analysis - Muhammad Iqbal Alias. (2009)
Every new construction of pressure vessels and boilers has been designed to ensure safe and reliable performance necessary during its operational life span. Understanding how the pressure vessel fails is one of key criteria to avert any unnecessary catastrophic accident. Applying the right tools in the design phase, will not only ensure reliability and safety but also promises uninterrupted business operation that is important to the operator’s perspective.